Is health promotion effective to control non-communicable disease? - Dewi, Khaerani Arista; Supriyati (BKM Public Health and Community Medicine, 2021)
Purpose: This study aims to assess the effectiveness of health promotion in controlling NCDs. Methods: This study was conducted using a literature review method. A search was performed on PubMed using the keywords "effective," "health promotion," and "NCD." The initial search yielded 51 articles, which were then screened and narrowed down to 10 articles published within the last five years. These selected articles were further reviewed and analyzed. A narrative synthesis was conducted based on the types of findings to present evidence on the effectiveness of health promotion in addressing non-communicable diseases (NCDs). Results: Health promotion has proven to be effective in reducing NCD risk factors, which include unhealthy eating patterns, tobacco use, physical activity, and alcohol use. The health promotion methods used include the use of media (i.e., TV, magazines, and leaflets), social media (WeChat), policies (healthy food labels and healthy schools), education on the importance of early physical activity, peer education programs through cadres, and community empowerment. Health promotion programs were carried out in communities, workplaces, and schools. This review suggested that schools were ideal places to instill healthy behaviors from an early age. Health promotion interventions also need to consider gender. Conclusion: Health promotion was effective in reducing risk factors when implemented using multiple methods simultaneously. Schools were recommended as a place to start developing positive habits that reduce NCD risk factors.